Vibration analysis of two-dimensional micromorphic structures using quadrilateral and triangular elements. Issue 5 (17th January 2022) - Kohansal Vajargah, Mina; Ansari, Reza
Abstract : Purpose: The paper aims to presents a numerical analysis of free vibration of micromorphic structures subjected to various boundary conditions. Design/methodology/approach: To accomplish this objective, first, a two-dimensional (2D) micromorphic formulation is presented and the matrix representation of this formulation is given. Then, two size-dependent quadrilateral and triangular elements are developed within the commercial finite element software ABAQUS. User element subroutine (UEL) is used to implement the micromorphic elements. These non-classical elements are capable of capturing the micro-structure effects by considering the micro-motion of materials. The effects of the side length-to-length scale parameter ratio and boundary conditions on the vibration behavior of 2D micro-structures are discussed in detail. The reliability of the present finite element method (FEM) is confirmed by the convergence studies and the obtained results are validated with the results available in the literature. Also, the results of micromorphic theory (MMT) are compared with those of micropolar and classical elasticity theories. Findings: The study found that the size effect becomes very significant when the side length of micro-structures is close to the length scale parameter. Originality/value: The study is to analyze the free vibrations of 2D micro-structures based on MMT; to develop a 2D formulation for micromorphic continua within ABAQUS; to propose quadrilateral and triangular micromorphic elements using UEL and to investigate size effects on the vibrational behavior of micro-structures with various geometries.